Analisis Prediksi Penjualan Wedang Uwuh Instan dengan Simulasi Algoritma Monte Carlo - Titik Rahmawati; Eka Yulia Sari; Agung Priyanto; V. Reza Bayu Kurniawan; Diyan Dewana Jaya (G-Tech: Jurnal Teknologi Terapan, 2024)
Traditional herbal drinks such as Wedang Uwuh which is a typical Yogyakarta regional drink made from various natural spices it has various benefits. Wedang Uwuh instant ​​is an innovative product from a traditional drink that is packaged in a modern way. Instant Wedang Uwuh is a product of creativity from Industrial Engineering students at the Faculty of Engineering, Universitas Sarjanawiyata Tamansiswa, which is managed by lecturers and students. The manager of instant Wedang Uwuh, PT Sruput Jaya, is experiencing difficulties in stock management and estimating the amount of production required each month. The uncertain demand for instant Wedang Uwuh is an obstacle in determining the production quantity of Instant Wedang Uwuh. Currently, sellers can only see the increase in sales manually. This research aims to predict the level of production or sales of Instant Wedang Uwuh using the Monte Carlo simulation algorithm precisely and accurately. The results of Monte Carlo simulation testing for 12 months reached a prediction accuracy level of 96.40%. The tests carried out will become a reference for preparing instant Wedang Uwuh production for the next 12 months. Obtaining an accuracy rate of 96.40% in this Monte Carlo simulation can be recommended for determining the amount of Wedang Uwuh production in the first 12 months of the following year.